Metode Image Streaming dalam Pembelajaran Menulis Sajak - Rusmana, Renaldi; Nugraha, Haris Santosa (LOKABASA, 2019)
Over time, students consider learning Sundanese in school increasingly difficult, especially in writing poetry learning material. The purpose of this study was to describe students poetry writing abilities before and after using the Image streaming method and the difference in students poetry writing abilities before and after using the Image Streaming method. This study uses a quantitative approach, the method used is quasi-experiment with one group pre-test and post-test research design, and the technique used is poetry writing ability test. The data source of this research is the ability to write poetry of class VII-E students at SMP 2 Lembang in the 2018-2019 school year, with 34 students. The results of this study show that: (1) the ability of students to write poetry before using the Image Streaming method with an average value of 57.56; (2) the ability of students to write poetry after using the Image Streaming method with an average value of 72.88; (3) differences in students poetry writing ability before and after using the Image Streaming method with an average initial ability score of 57.56, final ability of 72.88, then the average value of students poetry writing ability has increased by 15.32. Hypothesis test results show a significance value = 0,000. Based on the results of hypothesis testing, the value of Sig. 0,000 is smaller than 0.05, meaning H1 is accepted and H0 is rejected. Therefore, it can be concluded that the use of the Image Streaming method can improve the poetry writing ability of VII-E class students at SMPN 2 Lembang in the 2018-2019 school year.Â AbstrakSeiring berjalannya waktu, siswa menganggap pembelajaran bahasa Sunda di sekolah semakin sulit, khususnya dalam materi pembelajaran menulis sajak. Tujuan penelitian ini untuk mendeskripsikan kemampuan menulis sajak siswa sebelum dan setelah menggunakan metode Image Streaming dan perbedaan kemampuan menulis sajak siswa sebelum dan setelah menggunakan metode tersebut. Penelitian ini menggunakan pendekatan kuantitatif, dengan metode kuasi eksperimen disertai desain one group pre-test and post-test. Teknik yang digunakan adalah teknik tes dengan menggunakan soal tes kemampuan menulis sajak pada siswa kelas VII-E di SMP Negeri 2 Lembang pada tahun ajaran 2018/2019. Hasil dari penelitian ini menunjukkan: (1) kemampuan menulis sajak siswa sebelum menggunakan metode Image Streaming dengan rata-rata nilai 57,56; (2) kemampuan menulis sajak siswa setelah menggunakan metode Image Streaming dengan rata-rata nilai 72,88; (3) perbedaan kemampuan menulis sajak siswa sebelum dan setelah menggunakan metode Image Streaming dengan rata-rata nilai kemampuan awal 57,56, kemampuan akhir 72,88, maka rata-rata nilai kemampuan menulis sajak siswa mengalami peningkatan sebesar 15,32. Hasil uji hipotesis menunjukan nilai signifikansi = 0,000. Berdasarkan hasil uji hipotesis, nilai Sig. 0,000 lebih kecil dari 0,05, artinya H1 diterima dan H0 ditolak. Oleh sebab itu, dapat disimpulkan bahwa penggunaan metode Image Streaming dapat meningkatkan kemampuan menulis sajak siswa kelas VII-E di SMP Negeri 2 Lembang taun ajaran 2018-2019.